The Role of Feel, Act, and Price Fairness in Increasing Revisit Intention through Tourist Satisfaction and Trust Wahoo Waterworld Tourists - Abellya Febriyana; Yadi Ernawadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of experiential marketing (sense, feel, act) and price fairness on revisit intention of Wahoo Waterworld tourists through tourist satisfaction and trust using the stimulus–organism–response (SOR) framework. This quantitative study used a survey method on 140 tourists who had visited Wahoo Waterworld, West Bandung Regency, who were selected through purposive sampling. Data were collected using an online questionnaire and analyzed with PLS-SEM using SmartPLS 3.0. The results showed that tourist satisfaction and trust had a positive effect on revisit intention. The feel and act dimensions and price fairness had an indirect effect on revisit intention through tourist satisfaction, while price fairness also had an indirect effect through trust. These findings imply the need for managing emotional experiences, active involvement, and price fairness to increase tourist satisfaction and trust as prerequisites for revisit intention. Future research is recommended to add the think and relate dimensions and test the model on more diverse destinations and tourist segments.